Implementasi Bimbingan Konseling Islam terhadap Peningkatan Akhlak di Pondok Pesantren Hidayatullah Kota Palopo - Nilasari, Rini; Ayub, Ayub (IIQ An Nur Yogyakarta, 2024)
This study discusses the implementation of Islamic counselling guidance on improving morals at Hidayatullah boarding school in Palopo. The purpose of this research is to 1) find out the implementation of Islamic counselling guidance on the morals of students at Hidayahtullah boarding School and 2) find out the methods of Islamic guidance and counselling on the morals of Hidayatullah boarding school students. The type of research used is descriptive qualitative, which is research that describes facts or symptoms by collecting information described in the form of words or narratives using observation, interview, and documentation techniques. The results showed that the implementation of Islamic Guidance and Counseling was realized in the activities of congregational prayers in the mosque, the implementation of tahajud prayers in the mosque, the provision of studies or halaqah, the implementation of Monday-Thursday fasting, the formation of mosque cleaning pickets. With orientation methods, information, learning, special coaching, consultation, understanding, prevention, facilities and adjustments, maintenance and development